LAW ENFORCEMENT BY THE POLICE AGAINST JUVENILE BRAWLERS RESULTING IN FATALITIES: (CASE STUDY: PADEMANGAN POLICE STATION) - Kusuma, I Gede Gustiyana Wijaya (Universitas Airlangga, 2024)
Currently, the situation of the young generation is quite worrying, namely that almost every time in the mass media and electronic media there are reports of juvenile delinquency in the form of brawls between students and even crimes committed in the form of criminal acts of abuse or fighting, they have begun to abandon traditional methods of using wood or using force. physical, but now they have the courage to use sharp weapons which can not only result in injuries, they can even result in fatalities, as in one of the cases in the Pademangan District, North Jakarta. Looking at the examples of these cases, it can be said that brawls between students cannot be taken lightly, because if they are not handled seriously by the relevant parties, they will have a negative impact on the condition of students, the school environment and the community because the impact can also kill the lives of students who are still teenagers and has a long future. Therefore, there needs to be certainty in law enforcement by law enforcement officials to follow up on what punishments are given to perpetrators of brawls between students so that there is a deterrent effect and in the future there will be no more brawls between students. The research method used in this research is a qualitative method. The results of this research are that criminal law enforcement carried out by the Kademangan Police against perpetrators of brawls between students that resulted in death has basically been implemented, but the process from the identification stage to criminal action and the imposition of punishments needs to be effective. If law enforcement against students who engage in brawls is ineffective, this will result in the lack of legal certainty, order and legal protection. The obstacle in law enforcement is because the students are still minors, so the regulations used are still within the juvenile justice system. The results of the research show what sanctions are imposed on children who commit criminal acts and what the criminal responsibility of minors who commit murder is. First, the sanctions that can be imposed on minors who commit criminal acts are in accordance with what is regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, namely in the form of penalties and actions. Second, that the criminal responsibility of minors who commit murder is in accordance with the provisions regulated in the Criminal Code and Law no. 11 of 2012 concerning the Juvenile Criminal Justice System.